A nationwide population-based cohort study of surgical care for patients with superior sulcus tumors: Results from the Dutch Lung Cancer Audit for Surgery (DLCA-S). (November 2021) - Winkelman, J.A.; van der Woude, L.; Heineman, D.J.; Bahce, I.; Damhuis, R.A.; Mahtab, E.A.F.; Hartemink, K.J.; Senan, S.; Maat, A.P.W.M.; Braun, J.; Paul, M.A.; Dahele, M.; et al.
Highlights: The resection rate of sulcus superior tumors in the Netherlands is 14.4% 1% of all pulmonary resections for lung cancer is for sulcus superior tumors. Spontaneous centralisation of sulcus superior tumor surgery has occurred. Abstract: Objectives: Data on national patterns of care for patients with superior sulcus tumors (SST) is currently lacking. We investigated the distribution of surgical care and outcome for patients with SST in the Netherlands. Material and methods: Data was retrieved from the Dutch Lung Cancer Audit for Surgery (DLCA-S) for all patients undergoing resection for clinical stage IIB-IV SST from 2012 to 2019. Because DLCA-S is not linked to survival data, survival for a separate cohort (2015–2017) was obtained from the Netherlands Cancer Registry (NCR). Results: In the study period, 181 patients had SST surgery, representing 1.03% (181/17488) of all lung cancer pulmonary resections. For 2015–2017, the SST resection rate was 14.4% (79/549), and patients with stage IIB/III SST treated with trimodality had a 3-year overall survival of 67.4%. 63.5% of patients were male, and median age was 60 years. Almost 3/4 of tumors were right sided. Surgery was performed in 20 hospitals, with average number of annual resections ranging from ≤ 1 (n = 17) to 9 (n = 1). 39.8% of resections were performed in 1 center and 63.5% in the 3 most active centers. 12.7% of resections were extended (e.g. vertebral resection). 85.1% of resections were complete (R0). Morbidity and 30-day mortality were 51.4% and 3.3% respectively. Despite treating patients with a higher ECOG performance score and more extended resections, the highest volume center had rates of morbidity/mortality, and length of hospital stay that were comparable to those of the medium volume (n = 2) and low-volume centers (n = 1). Conclusion: In the Netherlands, surgery for SST accounts for about 1% of all lung cancer pulmonary resections, the number of SST resections/hospital/year varies widely, with most centers performing an average of ≤ 1/year. Morbidity and mortality are acceptable and survival compares favourably with the literature. Although further centralisation is possible, it is unknown whether this will improve outcomes.